Hovbroskförbening hos svenska ardennerhästen - Tullberg, Marja (2008)
Ossification of the collateral cartilages of the distal phalanx has been studied primarily in cold blooded horses. The clinical relevance of this condition is unknown. Despite this fact, since 1939, all Swedish Ardenner stallions have had to be classified as being free from this ossification to be approved for breeding. Initially, palpation was used as a diagnostic method, but since 1982 radiology has been the only method used.